Nixon's civil rights : politics, principle, and policy - Kotlowski, Dean J. (Harvard University Press, 2001)
Richard Nixon believed that history would show his administration in the forefront of civil rights progress. What does the record really say about civil rights under Nixon? In a groundbreaking new book, Dean Kotlowski offers a surprising study of an administration that redirected the course of civil rights in America. Nixon's policymaking recast the civil rights debate from an argument over racial integration to an effort to improve the economic station of disadvantaged groups. Kotlowski examines such issues as school desegregation, fair housing, voting rights, affirmative action, and minority businesses as well as Native American and women's rights. He details Nixon's role, revealing a president who favored deeds over rhetoric and who constantly weighed political expediency and principles in crafting civil rights policy. In moving the debate from the street to the system, Nixon set civil rights on a path whose merits and results are still debated. Nixon's Civil Rights is a revealing portrait of one of the most enigmatic figures of modern American politics and a major contribution to the study of civil rights in America.